A Comparative Chemical Study of Calcium Silicate-Containing and Epoxy Resin-Based Root Canal Sealers. (20th December 2016) - Reszka, Przemysław; Nowicka, Alicja; Lipski, Mariusz; Dura, Włodzimierz; Droździk, Agnieszka; Woźniak, Krzysztof
Abstract : Objective. The present study assessed the chemical elements in two novel calcium silicate-containing root canal sealers, BioRoot RCS and Well-Root ST, compared to a calcium silicate-containing root canal sealer that has been on the market for several years, MTA Fillapex, and epoxy resin-based sealer AHPlus. Material and Methods. The sealers were mixed and manipulated according to the manufacturers' instructions. Twelve cylindrical molds (inner diameter 4 mm; height 3 mm) were placed on a glass petri dish and packed with the materials. The dish was transferred to an incubator. After 72 h the molds were examined by scanning electron microscopy and energy dispersive X-ray microanalysis. Results. BioRoot RCS and Well-Root ST had high peaks of calcium, zirconium, oxygen, carbon, silicon, and chlorine. Well-Root ST also had sodium, magnesium, aluminum, and titanium peaks. MTA Fillapex and AHPlus had carbon, oxygen, calcium, titanium, and bismuth peaks. A silicon peak was also observed for MTA Fillapex, and zirconium and tungsten peaks for AHPlus. Conclusion. BioRoot RSC had the highest degree of purity. The clinical implication of metals contained in the other sealers needs to be investigated.